2004
DOI: 10.1189/jlb.0404248
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I stimulates IL-10 production in human T cells

Abstract: There is vast body of evidence that the insulin-like growth factor (IGF)-I exerts immunomodulatory effects in vitro and in vivo. In vitro studies indicate that stimulatory effects of IGF-I may be exerted through augmentation of inflammatory cytokine production. To further explore the immunomodulatory effects of IGF-I through regulation of cytokine production, we tested the in vitro effects of IGF-I on the secretion of inflammatory T helper cell type 1 (Th1) and Th2 cytokines by human peripheral blood mononucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…This growth factor was shown, for example, to play an important role in the differentiation (22,40) and survival (41,42) of oligodendrocytes and to be beneficial in the treatment of EAE (43,44). It seems reasonable to assume that the IGF-I produced by MG is responsible, at least in part, for the shift to a Th2 phenotype (45) and thus for the increased number of MHC class II + MG as well as of the newly formed BrdU + /MHC class II + MG expressing IGF-I. The increased oligodendrogenesis was found to correlate with a higher incidence of newly formed MHC class II + MG.…”
Section: Discussionmentioning
confidence: 99%
“…This growth factor was shown, for example, to play an important role in the differentiation (22,40) and survival (41,42) of oligodendrocytes and to be beneficial in the treatment of EAE (43,44). It seems reasonable to assume that the IGF-I produced by MG is responsible, at least in part, for the shift to a Th2 phenotype (45) and thus for the increased number of MHC class II + MG as well as of the newly formed BrdU + /MHC class II + MG expressing IGF-I. The increased oligodendrogenesis was found to correlate with a higher incidence of newly formed MHC class II + MG.…”
Section: Discussionmentioning
confidence: 99%
“…6a,b). Kooijman et al [23] reported that IGF-1 could stimulate IL-10, an important anti-inflammatory cytokine, production by activated normal human T cells. We hypothesized that the increased miR-223 levels could suppress IGF-1R expression, leading to impaired IL-10 production upon IGF-1 stimulation in RA T cells.…”
Section: Transfection Of Mir-223 Mimic Inhibited Igf-1-mediated Il-10mentioning
confidence: 99%
“…It stimulates TNFa, IL-8 and IL-6 secretion in human monocytes [9][10][11], IL-10 expression in T cells [12], and the production of interferon-c and IL-6 in neonatal mononuclear cells [13]. Since cytokines in the tumour microenvironment strongly influence cancer pathogenesis, a more detailed understanding of the regulatory mechanisms leading to cytokine expression in tumour cells may provide new opportunities to treat cancer.…”
Section: Introductionmentioning
confidence: 99%